Determinants of timing, adequacy and quality of antenatal care in Rwanda: a cross-sectional study using demographic and health surveys data - Gerard Uwimana; Mohamed Elhoumed; Mitslal Abrha Gebremedhin; Lin Nan; Lingxia Zeng (BMC, 2023)
Abstract Background Antenatal care (ANC) is a recommended intervention to lessen maternal and neonatal mortality. The increased rate in ANC coverage in most Sub-Saharan African countries is not considerably reducing the maternal and neonatal mortality. This disconnection has raised concerns to study further the trend and determinants of the ANC timing and quality. We aimed to assess the determinants and trend of the timing, the adequacy and the quality of antenatal care in Rwanda. Method A population-based cross-sectional study design. We used data from the 2010,2015 and 2020 Rwanda demographic and health surveys (RDHS). The study included 18,034 women aged 15-49 years. High quality ANC is when a woman had her first ANC visit within 3 months of pregnancy, had 4 or more ANC visits, received services components of ANC during the visits by a skilled provider. Bivariate analysis and multivariable logistic regression were used to assess the ANC (timing and adequacy), the quality of the content of ANC services and the associated factors. Results The uptake of antenatal services increased in the last 15 years. For instance, the uptake of adequate ANC was 2219(36.16%), 2607(44.37%) and 2925(48.58%) respectively for 2010;2015 and 2020 RDHS. The uptake of high quality ANC from 205(3.48%) in 2010 through 510(9.47%) in 2015 to 779(14.99%) in 2020. Women with unwanted pregnancies were less likely to have timely first ANC (aOR:0.76;95%CI:0.68,0.85) compared to planned pregnancies, they were also less likely to achieve a high-quality ANC (aOR: 0.65;95%CI:0.51,0.82) compared to the planned pregnancies. Mothers with a secondary and higher education were 1.5 more likely to achieve a high-quality ANC (aOR:1.50;95%CI:1.15,1.96) compared to uneducated mothers. Increasing maternal age is associated with reduced odds of update of ANC component services (aOR:0.44;95%CI:0.25,0.77) for 40 years and above when referred to teen mothers). Conclusion Low-educated mothers, advanced maternal age, and unintended pregnancies are the vulnerable groups that need to be targeted in order to improve ANC-related indicators. One of the credible measures to close the gap is to strengthen health education, promote family planning, and promote service utilization.